Edukasi Isu Lingkungan Pertambangan Terhadap Masyarakat, Untuk Menumbuhkan Karakter Peduli Lingkungan Pada Siswa SMA Negeri 2 Gorontalo Utara - Regina Putri Podu; Yayu Indriati Arifin; Nawir Sune (-, 2026)
This community service activity aims to increase students' understanding of the environmental impacts of mining activities and foster an environmentally conscious character among students at SMA Negeri 2 North Gorontalo. The background to this activity is based on the increasing number of environmental problems caused by mining activities, such as water pollution, land degradation, declining air quality, and ecosystem degradation. Therefore, educational efforts are needed to raise awareness among the younger generation about the importance of environmental conservation. The method used in this activity is participatory outreach and education through material delivery, interactive discussions, questions and answers, and motivation related to environmentally friendly behavior. The target group for this activity was 30 students at SMA Negeri 2 North Gorontalo. Evaluation of the activity was conducted through observation, documentation, and the distribution of questionnaires to measure the level of understanding of participants after participating in the activity. The results showed that students responded very positively and demonstrated a high level of participation throughout the program. Based on the questionnaire results, 80% of students were in the high understanding category, 13.33% in the medium category, and 6.67% in the low category. These findings indicate that the educational activity successfully increased students' knowledge of environmental issues in mining while fostering environmental awareness and character. Thus, environmental education based on mining issues can be an effective strategy for developing environmental literacy, ecological awareness, and environmental responsibility in the younger generation as part of efforts to achieve sustainable development.